Exploring Surgeons', Nurses', and Patients' Information Seeking Behavior on Medical Innovations: The Case of 3D Printed Biodegradable Implants in Breast Reconstruction. Issue 2 (14th June 2022) - Whyte, Stephen; Bray, Laura; Chan, Ho Fai; Chan, Raymond J.; Hunt, Jeremy; Peltz, Tim S.; Dulleck, Uwe; Hutmacher, Dietmar W.
Abstract : Objectives: To explore information seeking behavior on medical innovations. Background: While autologous and alloplastic options for breast reconstruction are well established, it is the advent of the combination of 3D printing technology and the biocompatible nature of a highly porous biodegradable implants that offers new treatment options for the future. While this type of prosthesis is not yet clinically available understanding how patients, surgeons, and nurses take up new medical innovations is of critical importance for efficient healthcare provision. Materials and Methods: Using the largest ever combined sample of breast cancer patients (n = 689), specialist surgeons (n = 53), and breast care nurses (n = 101), we explore participants preference for a new surgical treatment concept rooted in 3D printed and biodegradable implant technologies in the context of breast reconstruction. Results: We find that patients overwhelmingly favor information from a successful patient of the proposed new technology when considering transitioning. Surgeons and nurses instead favor regulatory body advice, peer-reviewed journals, and witnessing the procedure performed (either in person or online). But while 1 in 4 nurses nominated talking to a successful patient as an information source, not a single surgeon chose the same. Our multinomial logit analysis exploring patient preference (controlling for individual differences) showed statistically significant results for both the type of surgical treatment and choice to undergo reconstruction. Women who underwent a type of mastectomy procedure (compared with lumpectomy patients) were more likely to choose a former patient than a surgeon for seeking information relating to a new breast implant technology. Further, women who chose to undergo a reconstruction procedure, compared with those who did not, where more likely to prefer a surgeon for information relating to a new breast implant technology, rather than a successful patient. For medical professionals, we find no statistically significant relationship between medical professionals' preference and their age, nor the number of other medical professionals they work with daily, nor the average number of breast procedures performed in their practice on a weekly basis. Conclusions: As our findings show large variation exists (both within our patient group and compared with medical professionals) in where individuals favor information on new medical innovations, future behavioral research is warranted.